Primer on the metabolic bone diseases and disorders of mineral metabolism. - Bilezikian, John P. (Hoboken, NJ : Wiley-Blackwell, 2019)
'Primer on the Metabolic Bone Diseases and Disorders of Mineral Metabolism, 9th Edition is the comprehensive revision of the field-leading reference on bone and mineral health. The eighth edition has been fully revised by the leading researchers and clinicians in the field to provide concise coverage of the widest possible spectrum of metabolic bone diseases and disorders of mineral metabolism. Chapters look to explain basic biological factors of healthy development and disease states and make it easily translatable to clinical interventions. Primer on the Metabolic Bone Diseases and Disorders of Mineral Metabolism is the definitive, one-stop reference for anyone working in the field of bone health and disease'--
'Sales handles: - Comprehensive coverage of key diseases of the bone and disorders of mineral metabolism * Invaluable clinical and basic research information in quick reference format -- Discipline leading reference -- Contributed by the world's foremost clinicians and researchers in bone and mineral metabolism -- New full color format Market description: Bone and mineral researchers, clinicians, dentists, oral surgeons, orthopedists, cancer researchers, oncologists, cellular and molecular biologists, endocrinologists'--
Print version record and CIP data provided by publisher; resource not viewed.
Includes bibliographical references and index.
Keywords: Bones -- Metabolism -- Disorders; Mineral metabolism -- Disorders; Bones -- Diseases; Minerals -- Metabolism; SCIENCE / Life Sciences / Cytology; Bones -- Diseases; Bones -- Metabolism -- Disorders; Mineral metabolism -- Disorders; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Electronic books